Integration of RAM Model and DES Method in Assessing Plant Utilization - Hassan, Muhamad Shukri (IRC, 2020)
This Final Year Project (FYP) entitled Integration of RAM Model and DES Method in Assessing Plant Utilization. Main motivation of this project is about plant utilization in oil and gas refinery plant. Plant utilization is an important indicator for a company to measure the production rate, operation safety and operation’s availability. Nevertheless, the percentage of plant utilization will be reduced due to the unplanned operation shutdown and slowdown. Basically, the unplanned shutdown occurs when the production units completely stopped unexpectedly due to failure of major components in main equipment which required a significant of time to repair. Meanwhile, the unit slowdown means the production unit incapable to produce the targeted number of products per day. It is quite tough for the company to cater these unfavourable events because there are numerous of production unit, equipment and components in the refinery plant. Thus, this study had focused to assess the plant utilization of oil and gas refinery by using two approaches to model the performance of refinery plant which are RAM model and DES method.